AN ANALYSIS OF CONTEXTUAL MEANING IN BATAK TOBA SONGS LYRIC BY PUTRI SILITONGA: A CASE ON SEMANTICS - Eni Julita Br Munthe; Maria A. Simamora; Herman; Fenti Debora Napitupulu; Christina Natalina Saragi (American Journals Publishing, 2022)
This research deals with the analysis of the contextual meaning of Batak Toba song lyrics by Putri Silitonga. This research was conducted using a descriptive qualitative research method. The researcher collected the data through observation and documentation. The data were taken from five songs of Putri Silitonga's “sweet song” album. The theory used was the theory of contextual meaning proposed by Mansoer Pateda (2010). There were eight types of contextual meaning found in the data namely, the context of the organ (11%), the context of formality (3%), the context of purpose and context object (17%), the context of mood (31%), and the context of time and context language (6%). The most dominant type of contextual meaning used in the research data is the context of mood, which is the percentage (31%). The result shows that context in the song plays an important role in determining the meaning of song lyrics.
Keywords: Contextual Meaning, Types of Context, Song lyric